Optimalisasi Kemampuan Menulis Teks Eksplanasi dan Keaktifan Siswa Kelas 11 Melalui Model Pembelajaran Problem Based Learning - Simanjuntak, Hanna Maria; Telaumbanua, Sadieli; Perangin-Angin, Esra (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This study aims to explore the effect of Problem-Based Learning Model (PBL) on the learning outcomes of students in grade XI of SMAN 4 Medan in writing an explanatory text in Indonesian language subject. By focusing on the effectiveness of PBL in improving students' writing skills, this study provides theoretical contributions to the development of learning theories as well as practical benefits for teachers and schools in improving the quality of learning.Method – The study used a quasi-experimental design with an experimental group and a control group. The approach was Problem Based Learning (PBL) Model. The research was conducted at SMAN 4 Medan involving students of grade XI. Data were collected through an explanatory text writing test conducted before (pretest) and after (posttest) the application of PBL. The analysis was conducted by comparing the posttest results between the experimental group using PBL and the control group using conventional learning methods. The results were analyzed to assess the effectiveness of PBL in improving students' writing ability.Findings – The results showed that the Problem-Based Learning Model (PBL) significantly improved students' learning outcomes in writing explanatory texts. Proven by the average value of posttest in the experimental group which is higher than the control group, which proves the effectiveness of PBL in the context of Indonesian language learning in class XI SMAN 4 Medan. Research Implications – The Problem-Based Learning (PBL) model enhances students' writing skills in explanatory texts at the senior high school level. This study, limited to one school, does not reflect broader educational variations in Indonesia. It focused solely on PBL's impact on writing skills without a thorough exploration of other influencing factors. Future research should expand the sample size and include diverse contextual elements to more robustly verify these results.